The 5.2 ka climate event: Evidence from stable isotope and multi-proxy palaeoecological peatland records in Ireland - Roland, TP; Daley, TJ; Caseldine, CJ; Charman, DJ; Turney, CSM; Amesbury, MJ; Thompson, GJ; Woodley, EJ (Quaternary Science Reviews, 2015)
This is the author accepted manuscript. The final version is available from Elsevier via the DOI in this record. Evidence for a major climate event at 5.2 ka has been reported globally and is associated with considerable societal disruption, but is poorly characterised in northwest Europe. This event forms part of a broader period of re-organisation in the Earth's ocean-atmosphere circulation system between 6 and 5 ka. This study tests the nature and timing of the event in northwest Europe, a region highly sensitive to change in meridional overturning circulation and mid-latitude westerly airflow. Here we report three high-resolution Irish multi-proxy records obtained from ombrotrophic peatlands that have robust chronological frameworks. We identify the 5.2 ka event by a sustained decrease in δ 18 O cellulose at all three sites, with additional and parallel changes in δ 13 C cellulose and palaeoecological (testate amoebae, plant macrofossil and humification) data from two sites in northern Ireland. Data from Sluggan Moss demonstrate a particularly coherent shift towards wetter conditions. These data support the hypothesis that the event was caused by a prolonged period of positive North Atlantic Oscillation conditions, resulting in pervasive cyclonic weather patterns across northwest Europe, increasing precipitation over Ireland. This research was carried out while T.P.R. held UK Natural Environment Research Council studentship at the University of Exeter (NE/G524328/1) and T.J.D held a studentship at the University of Southampton tied to the NERC RAPID Programme (NER/T/S/2002/00460). Radiocarbon support was provided by the NERC 14C Steering Committee (Allocation No.: 1523.0910), the NERC RAPID Programme and the Irish Quaternary Association via the IQUA Bill Watts 14Chrono award.